Axillary accessory breast carcinoma masquerading as axillary abscess: a case report - Lim, Shu Yu; Jee, Shir Lee; Gee, Tikfu; Emran, Nor Aina (Malaysian Medical Association, 2016)
Accessory breast is a frequently seen developmental breast abnormality, commoner among Asians than Caucasians. This ectopic breast tissue shares many similarities as the normal breast tissue, and although subjected to the same pathological processes, accessory breast carcinoma is rare. As locations of the accessory breast may be variable, detection of pathological lesions through clinical examinations and standard diagnostic tools (i.e., mammogram) can be difficult. Staging and management should be tailored-made according to the location of the accessory breast as well as its known pattern of lymphatic drainage. We report a case of an intra-ductal carcinoma occurring in an axillary accessory breast.